Muscle damage, inflammatory, immune and performance responses to three football games in 1 week in competitive male players - Mohr, M.; Draganidis, D.; Chatzinikolaou, A.; Barbero-Álvarez, J. C.; Castagna, C.; Douroudos, I.; Avloniti, A.; Margeli, A.; Papassotiriou, I.; Flouris, A. D.; Jamurtas, A. Z.; Krustrup, P.; et al. (European Journal of Applied Physiology, 2016)
Purpose: We examined effects of a three-game, 1-week microcycle (G1, G2, G3) on recovery of performance and inflammatory responses in professional male footballers. Methods: Players were randomized into an experimental (EXP; N = 20) and a control group (CON; N = 20). Blood was drawn and repeated sprint ability (RSA), muscle soreness and knee range of motion (KJRM) were determined pre- and post-games and during recovery. Results: High-intensity running during G2 was 7-14 % less compared to G1 and G3. RSA declined in EXP by 2-9 % 3 days post-game with G2 causing the greatest performance impairment. In EXP, game play increased muscle soreness (~sevenfold) compared to CON with G2 inducing the greatest rise, while KJRM was attenuated post-game in EXP compared to CON (5-7 %) and recovered slower post G2 and G3 than G1. CK, CRP, sVCAM-1, sP-Selectin and cortisol peaked 48 h post-games with G2 eliciting the greatest increase. Leukocyte count, testosterone, IL-1ß and IL6 responses, although altered 24 h post each game, were comparable among games. Plasma TBARS and protein carbonyls rose by ~50 % post-games with G2 eliciting the greatest increase 48 h of recovery. Reduced to oxidized glutathione ratio declined for 24 h post all games with G2 displaying the slowest recovery. Total antioxidant capacity and glutathione peroxidase activity increased (9-56 %) for 48 h in response to game play. Conclusion: In summary, post-game performance recovery and inflammatory adaptations in response to a three-game weekly microcycle displayed a different response pattern, with strong indications of a largest physiological stress and fatigue after the middle game that was preceded by only a 3-day recovery.